2020
DOI: 10.1084/jem.20200471
|View full text |Cite
|
Sign up to set email alerts
|

Imaging resident and recruited macrophage contribution to Wallerian degeneration

Abstract: Wallerian degeneration (WD) is a process of autonomous distal degeneration of axons upon injury. Macrophages (MPs) of the peripheral nervous system (PNS) are the main cellular agent controlling this process. Some evidence suggests that resident PNS-MPs along with MPs of hematogenous origin may be involved, but whether these two subsets exert distinct functions is unknown. Combining MP-designed fluorescent reporter mice and coherent anti–Stokes Raman scattering (CARS) imaging of the sciatic nerve, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Gene expression changes following peripheral nerve injury have been extensively studied by microarray analysis and bulk mRNA sequencing (Arthur-Farraj et al, 2012 , 2017 ; Fontana et al, 2012 ; Jessen and Mirsky, 2016 ; Clements et al, 2017 ; Gokbuget et al, 2018 ; Norrmen et al, 2018 ; Stratton et al, 2018 ; Tomlinson et al, 2018 ; Boissonnas et al, 2020 ; Ydens et al, 2020 ). However, cell type specific gene expression changes have not been studied.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression changes following peripheral nerve injury have been extensively studied by microarray analysis and bulk mRNA sequencing (Arthur-Farraj et al, 2012 , 2017 ; Fontana et al, 2012 ; Jessen and Mirsky, 2016 ; Clements et al, 2017 ; Gokbuget et al, 2018 ; Norrmen et al, 2018 ; Stratton et al, 2018 ; Tomlinson et al, 2018 ; Boissonnas et al, 2020 ; Ydens et al, 2020 ). However, cell type specific gene expression changes have not been studied.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are no clear markers to distinguish activated resident macrophages from infiltrated macrophages in injured nerves (Amann and Prinz, 2020 ; Kolter et al, 2020 ). A recent publication using both Csf1r-ECFP and Cx3cr1-EGFP mice demonstrated that resident macrophages have distinct function and morphological difference from recruited macrophages (Boissonnas et al, 2020 ). Macrophages in the distal nerve could be identified with macrophage marker genes Aif1/Iba1, Cd68, and Mrc1/Cd206.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latent phase lasts up to 36 h wherein the axons appear normal and for much of this time retain the ability to conduct an action potential, although the axon becomes committed to degenerate ( Tsao et al, 1999 ; Beirowski et al, 2004 ; Beirowski et al, 2005 ; Conforti et al, 2014 ). This is also the stage in which the immune system is first seen to be involved; tissue-resident macrophages are activated and bone-marrow derived macrophages, neutrophils and phagocytes infiltrate into the nerve ( Perkins and Tracey, 2000 ; Sta et al, 2014 ; Zigmond and Echevarria, 2019 ; Boissonnas et al, 2020 ; Ydens et al, 2020 ; Chen et al, 2021 ). There is also an injury-associated increase in the levels of cytokines ( Yi et al, 2017 ).…”
Section: Axon Degeneration Research From 1850 To Todaymentioning
confidence: 99%
“…The axons fragment and the compound action potential is lost as they become non-functional ( Beirowski et al, 2004 ; Beirowski et al, 2005 ; Conforti et al, 2014 ; Sta et al, 2014 ). Neutrophils may contribute in the early stages of the execution of degeneration by phagocytosing axonal debris ( Lindborg et al, 2017 ), whilst macrophages clear myelin and axonal debris and later are involved in the axon regeneration process ( Boissonnas et al, 2020 ).…”
Section: Axon Degeneration Research From 1850 To Todaymentioning
confidence: 99%